The phases of user experience during relocation to a smart office building: A qualitative case study - Tuzcuoglu, Deniz; Yang, Dujuan; de Vries, Bauke; Sungur, Asli; Appel-Meulenbroek, Rianne (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2021)
Smart office concepts became popular in recent decades, and organisations adopt this concept with expected benefits on users. Yet, it is unclear how users experience the relocation process to a smart office environment. This study examines user experiences during such relocation by focusing on their behaviour and satisfaction. Eleven semi-structured interviews were conducted with users after relocation to a smart office building of a Dutch Municipality. The data were analysed based on grounded theory and thematic analysis. The results reveal that the process of experiencing a smart office environment consisted of four phases: pre-relocation phase, confrontational phase, progressive phase, and stabilised phase. Each participant experienced the process differently as four different trend lines emerged related to their interpreted emotional responses throughout this process. This study concludes by advocating that the understanding of user behaviour in each phase is crucial to enhance user satisfaction when moving into a smart office. The phases further highlight the importance of understanding user expectations, and the relationships between users and workplaces before and after the relocation.
Keywords: Smart office; User behaviour; Satisfaction; Expectation; Relocation; OPEN-PLAN OFFICE; CHANGE MANAGEMENT; WORKPLACE; ENVIRONMENT; WORKSPACE; PERFORMANCE; EMPLOYEES; BENEFITS; WORKING; Environmental Sciences & Ecology; Psychology